RESPONSIBILITY OF PUBLIC HEALTH SERVICE BASED ON THE CONSTITUTION OF INDONESIA - Ardiansah Ardiansah (Fakultas Hukum, Universitas Diponegoro, 2020)
The Indonesian Constitution has mandated health services for its people. Everyone has the right to receive health services, while the state is obliged to provide health services. The implementation of public health services faces problems concerning the president regulations about the increase of health insurance fee. The House of Representatives does not agree with the increase in health insurance fee, because the government should be responsible for the realization of public health services. This research uses normative legal research methods. The results showed that the government's policy of raising fees was considered unfair and burdensome to the people of Indonesia.Health services for the people of Indonesia has been mandated by The Indonesian Constitution. The denial of health services is a violation to the Indonesian constitution. The people have the right to get health services, whereas the state is responsible for providing health services. Therefore, even though the government raises fees, people expect the government to cancel the increase of the fee. Due to the fact that the Indonesian constitution has made it clear that the state is responsible for providing health services to its people.